Skeletal Muscle Fatigability in Heart Failure - Keller-Ross, Manda L.; Larson, Mia; Johnson, Bruce D (Frontiers in Physiology, 2019)
Evidence suggests that heart failure (HF) patients experience skeletal muscle fatigability in the lower extremity during single-limb tasks. The contribution of skeletal muscle fatigability to symptoms of exercise intolerance (perceived fatigue and dyspnea) is relatively unclear. Symptomatic or ‘perceived’ fatigue is defined by the sensations of exhaustion or tiredness that patients experience either at rest or while performing a motor task. Although factors that contribute to symptoms of fatigue in patients with HF are multifactorial; the skeletal muscle likely plays a major role. Skeletal muscle fatigability, as opposed to symptomatic fatigue, is an objective measure of a reduction in muscle force or power or reduced ability of the muscles to perform over time. Indeed, evidence suggests that patients with HF experience greater skeletal muscle fatigability which may contribute to a diminution in motor performance and the overall symptomatology that is hallmark of exercise intolerance in HF. This review will discuss 1) skeletal muscle fatigability in patients with HF, 2) the mechanisms contributing to locomotor skeletal muscle fatigability in HF and 3) the relationship of fatigability to symptoms of perceived fatigue and exercise intolerance in HF patients. Evidence suggests that cardiac dysfunction alone does not contribute to exercise intolerance. Therefore, mechanisms of skeletal muscle fatigability and their contribution to symptoms of fatigue and exercise intolerance, is an increasingly important consideration as we develop rehabilitative strategies for improving motor performance and functional capacity in patients with HF.